2010
DOI: 10.1007/s11081-010-9107-1
|View full text |Cite
|
Sign up to set email alerts
|

Global optimization of robust truss topology via mixed integer semidefinite programming

Abstract: This paper discusses a global optimization method of robust truss topology under the load uncertainties and slenderness constraints of the member crosssectional areas. We consider a non-stochastic uncertainty of the external load, and attempt to minimize the maximum compliance corresponding to the most critical load. A design-dependent uncertainty model in the external load is proposed in order to consider the variation of truss topology rigorously. It is shown that this optimization problem can be formulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…It can be found that, among totally 51 binary discrete variables, the optimal values of 18 0-1 variables (x i , i ∈ I 1 = {5, 9,10,14,15,17,19,22,24,27,28,32,33,38,40,43,45, 50}) can be determined directly in the first-round sensitivity bounding analysis. With these obtained values being fixed another 15 values of x i , i ∈ I 2 = {1, 4,12,13,18,20,23,26,29,34,35,37, 39, 48, 51} can be found from monotonic analysis in the second-round sensitivity bounding process. After that, the 0-1 programming with 18 remaining variables is solved by the optimizer CPLEX with global optimality.…”
Section: A 51-bar Truss Arch Bridgementioning
confidence: 99%
“…It can be found that, among totally 51 binary discrete variables, the optimal values of 18 0-1 variables (x i , i ∈ I 1 = {5, 9,10,14,15,17,19,22,24,27,28,32,33,38,40,43,45, 50}) can be determined directly in the first-round sensitivity bounding analysis. With these obtained values being fixed another 15 values of x i , i ∈ I 2 = {1, 4,12,13,18,20,23,26,29,34,35,37, 39, 48, 51} can be found from monotonic analysis in the second-round sensitivity bounding process. After that, the 0-1 programming with 18 remaining variables is solved by the optimizer CPLEX with global optimality.…”
Section: A 51-bar Truss Arch Bridgementioning
confidence: 99%
“…From an optimization perspective, mixed-integer semi-definite optimization (MI-SDP) has received a lot of attention in recent years, for they naturally appear in robust optimization problems with ellipsoidal uncertainty sets [4] or as reformulations of combinatorial problems [58]. Problem-specific MI-SDP strategies have been developed for problems such as binary quadratic programming [33], robust truss topology [63] or the max-cut problem [51]. More recently, rounding and Gomory cuts [12,1], branch-and-bound [29] and outer-approximation schemes [43] have also been developed, in an attempt to provide the same level of general-purpose solvers for MI-SDP as there are for mixed-integer linear optimization.…”
Section: Current Approachesmentioning
confidence: 99%
“…Guna-wa和Azarm [25~27] 提出一种新的区间参数灵敏度评估方 法, 并将该方法推广到单目标和多目标的鲁棒性优化 问题中. 为了获得带有区间参数鲁棒性优化的全局最 优解, Yonekura和Kanno [28] 采用分支定界方法处理桁 架结构鲁棒性拓扑优化问题. Siddiqui等人 [29] 通过在 原有的Bender's分解方法中增加额外的鲁棒性判断, 将Bender's分解方法拓展到区间非线性鲁棒性优化问 题中, 提高了鲁棒性优化问题的求解效率.…”
Section: 因此 在不确定性领域发展了一种非概率不确定unclassified